2008
DOI: 10.1177/0148607108319804
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Measurements Accurately Represent Trends in Resting Energy Expenditure in Children Undergoing Hematopoietic Stem Cell Transplantation

Abstract: Background Resting energy expenditure (REE) measurements are optimal for accurate assessment of energy requirements and precise provision of parenteral nutrients. We previously observed significant reduction in REE during a 4-week period in children undergoing hematopoietic stem cell transplantation (HSCT). The goal of this study was to determine if weekly REE measurements could accurately represent changes in REE in the peritransplant period compared with a more frequent standard of daily measurements. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These fluctuations may be attributed to type of conditioning regimen (total body irradiation, chemotherapy), fever, mucositis, engraftment, posttransplant complications such as GVHD, and lean muscle mass. 16,[36][37][38] The use of indirect calorimetry for estimation of energy needs is considered the criterion standard and may be warranted in this population. This recommendation is made in light of the fluctuation of energy needs over time, inaccuracy in energy equations, and changes in lean muscle mass and fluid shifts that occur.…”
Section: Determination Of Energy Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These fluctuations may be attributed to type of conditioning regimen (total body irradiation, chemotherapy), fever, mucositis, engraftment, posttransplant complications such as GVHD, and lean muscle mass. 16,[36][37][38] The use of indirect calorimetry for estimation of energy needs is considered the criterion standard and may be warranted in this population. This recommendation is made in light of the fluctuation of energy needs over time, inaccuracy in energy equations, and changes in lean muscle mass and fluid shifts that occur.…”
Section: Determination Of Energy Requirementsmentioning
confidence: 99%
“…Pediatric patients (0–18 years of age) undergoing HSCT therapy may experience fluctuations in energy requirements throughout the continuum of care. These fluctuations may be attributed to type of conditioning regimen (total body irradiation, chemotherapy), fever, mucositis, engraftment, posttransplant complications such as GVHD, and lean muscle mass 16,36–38 . The use of indirect calorimetry for estimation of energy needs is considered the criterion standard and may be warranted in this population.…”
Section: Mnt: Screening Nutrition Assessment and Determination Of Mnt...mentioning
confidence: 99%
“…Most studies investigating energy expenditure by indirect calorimetry have been performed in small paediatric populations. Validity of the data for adults therefore is limited, and results are controversial (Sharma et al 2012;Duro et al 2008).…”
Section: Estimation Of Caloric Needsmentioning
confidence: 99%
“…19 Duro et al 20 observed significant reduction in resting energy expenditure (REE) during a 4-week period in children undergoing HSCT. Although the amount of energy expended by a patient with HSCT may vary according to whether it is autologous or allogeneic, there is agreement as to the energy requirements of the transplant recipient, which may increase up to 130-150% of the estimated basal energy expenditure, which corresponds to 30-50 kcal/kg of body weight per day.…”
Section: Dietary Energymentioning
confidence: 99%